The Relationship Between Hemoglobin Levels And Wound Healing Post Sectio Caesarea At RSUD Rantau Prapat - Siburian, Christine Handayani; Naibaho, Eka Nugraha V; Silaban , Nataria Yanti (SEAN Institute, 2023)
Sectio caesarea or cesarean section is an operation that aims to remove the baby through an incision in the abdominal wall and uterine wall provided that the uterus is intact and the fetal weight is above 500 grams. This study aims to analyze the relationship between hemoglobin levels and post-sectio caesarea wound healing at RSUD Rantau Prapat. The type of research used is quantitative with an observational research design with a prospective cohort approach. The research was conducted in July 2021 at RSUD Rantau Prapat. The population in this study was all post sectio caesarea patients treated in June-July 2021. The population in this study was 27 people. The sampling technique in this study is a total sampling technique so that the number of samples in this study is 27 people. The results of the study conducted with the chi square test were obtained p values of 0.001 <0.05, meaning that there was a statistically significant relationship between hemoglobin levels and wound healing sectio caesarea at RSUD Rantau Prapat. It is recommended to health workers to take blood hemoglobin in patients sectio caesarea twice at 24 hours after sectio caesarea surgery, and at the time of control at the obstetric poly a week after surgery.